2020
DOI: 10.1016/s2542-5196(20)30227-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of PM2·5 on neurological disorders in the American Medicare population: a longitudinal cohort study

Abstract: Summary Background Accumulating evidence links fine particulate matter (PM 2·5 ) to premature mortality, cardiovascular disease, and respiratory disease. However, less is known about the influence of PM 2·5 on neurological disorders. We aimed to investigate the effect of long-term PM 2·5 exposure on development of Parkinson’s disease or Alzheimer’s disease and related dementias. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 33 publications
10
155
2
4
Order By: Relevance
“…2016 ). However, a recent nationwide study using information on Medicare enrollees, reported higher estimates in women for both AD and PD ( Shi et al. 2020 ), in agreement with other studies that also reported stronger associations of exposure with risk ( Liu et al.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…2016 ). However, a recent nationwide study using information on Medicare enrollees, reported higher estimates in women for both AD and PD ( Shi et al. 2020 ), in agreement with other studies that also reported stronger associations of exposure with risk ( Liu et al.…”
Section: Discussionsupporting
confidence: 84%
“…Medicare enrollees, reported higher estimates in women for both AD and PD (Shi et al 2020), in agreement with other studies that also reported stronger associations of PM 2:5 exposure with risk (Liu et al 2016) and aggravation (Lee et al 2017) of PD among females relative to males. Conversely, a study in a cohort of female nurses reported a null association between PM 2:5 and PD (Palacios et al 2014).…”
Section: Environmental Health Perspectivessupporting
confidence: 90%
See 3 more Smart Citations